Anisocoria in an intubated patient with COVID-19. Issue 7 (22nd July 2021) - Myers, Sam; Bhalla, Minak; Jolly, Rohit; Jain, Saurabh
Abstract : The effects of COVID-19 on the eye are still widely unknown. We describe a case of a patient who was intubated and proned in the intensive care unit (ICU) for COVID-19 and developed unilateral anisocoria. CT venogram excluded a cavernous sinus thrombosis. MRI of the head showed microhaemorrhages in the midbrain where the pupil reflex nuclei are located. After the patient was stepped down from ICU, intraocular pressure (IOP) was found to be raised in that eye. A diagnosis of subacute closed angle glaucoma was made. It is important for clinicians to rule out thrombotic causes in patients who develop acute anisocoria. It is also crucial to measure IOP in patients who develop ophthalmic pathology and have been proned for extended periods.